Analysis and intervention of heatwave related economic loss: Comprehensive insights from supply, demand, and public expenditure into the relationship between the influencing factors. (15th January 2023) - Wang, Peng; Zhang, Wendi; Liu, Jiawen; He, Pan; Wang, Jiaming; Huang, Lei; Zhang, Bing
Abstract: Increasing extreme temperatures are producing a serious impact on the economies of cities. However, the importance of social factors is typically neglected by the existing research. In this work, we first establish a supply-demand-public expenditure (SDP) framework for assessing and forecasting heat-related economic loss. Compared with the previous framework, SDP possesses a more comprehensive index system and functions that apply to all types of cities. We selected different economic development and geographical locations (Nanjing, Suzhou, and Yancheng) as case studies to verify the wide applicability of the SDP framework. A qualitative analysis and quantitative prediction of heatwaves and socioeconomic factors on losses were conducted for different cities. The results showed that different loss types displayed obvious regional heterogeneity among the cities. The labor value loss was the most significant type, and health loss was the most vulnerable type. In addition, public expenditure played a neglected critical regulatory role. Apart from these, the current level of public expenditure for heat prevention and control remains insufficient. Based on an assessment of the effects of interventions, policymakers need to make more efforts to increase the proportion of heat-related public spending and ensure stable socio-economic development by utilizing pathways with positive intervention potentials. Graphical abstract: Image 1 Highlights: Propose a new heat-related economic loss assessment framework. Comprehensively analyze the relationship between loss types and influence factors. Qualitatively and quantitatively analyze heat-related loss based on influence path. Suggestions are made considering characteristics and heterogeneity of loss.